Inclusive education in the Freirean perspective (Research, Society and Development, 2022)
Inclusive education is constituted as a sociopolitical movement that contemplates oppressed, discriminated and marginalized social groups in the social system, which fight for the principle of equity, in order to guarantee access to effective actions that recognize and value them as subjects of rights. Therefore, as a problem question: what are Paulo Freire's theoretical-methodological contributions to the concept of inclusive education? This article aims to analyze Paulo Freire's theoretical-methodological contributions to the concept of inclusive education. The methodology is based on a qualitative approach to understand the theoretical movement of the subject in question. Our study is of the bibliographic type, since we selected articles, books, theses and and records that covered the discussion of the theoretical framework. The respective authors are: Carvalho (2004), Freire (1996, 2014, 2016, 2018); Coast; Turci (2011); Marquez (2007). The results show that Paulo Freire's inclusive pedagogy is relevant and current for the conjuncture in which we are living, because his ideas become present for us to reflect and articulate socio-educational actions that promote the recognition and appreciation of otherness in the socio-educational context. Finally, it is clear that Paulo Freire's dialogical, liberating, humanized and progressive perspective is a form of inclusive education that builds an inclusive society for multiple differences.